IDENTIFIKASI MISKONSEPSI CALON GURU FISIKA PADA MATERI LISTRIK DINAMIS MENGGUNAKAN INSTRUMEN EDCT (ELECTRIC DYNAMIC CONCEPT TEST) DENGAN CRI (CERTAINTY OF RESPONSE INDEX) - Daimul Hasanah (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2017)
This research aimed to identify the misconceptions of physics teacher candidates in dynamic electrical materials using EDCT (Electric Dynamic Concept Test) instruments with CRI (Certainty of Response Index). This research included analytical descriptive research with 28 research subjects from Physics Education Departement, FKIP UST Yogyakarta. This research was conducted at the end of the even semester of 2015/2016 academic year. The instrument used in this research was in multiple choice test form with four alternative answers that have been completed with CRI. Item test was about 25 questions. The results of this study indicated that the students who mastered the concept was about 21.43%, the students who did not know the concept was about 21.43%, and the students who experienced misconception was about 57.14%.Keywords : miskonsepsi, dinamic electric, EDCT instrument, CRI.